Variations In Composition and Activity of Matricaria Pubescens (Desf.) Schultz Harvested from Different Regions in Algeria - Mohammed Tahar Tahar BEN-MOUSSA; Ammar OUAHAB; Hassina HARKAT; Samia LEKHEL; Youcef HADEF (ASM Science Journal, 2023)
Matricaria pubescens is traditionally used as a postpartum antihemorrhagic and to treat digestive disorders. The aim of this study is to determine the total amounts of phenols, flavonoids, condensed tannins, hydrolysable tannins, anthocyanins and total antioxidant capacity of samples from different regions and periods in Algeria in order to guide the selection of varieties and the period of harvest. The analysis was carried out by Ferric reducing antioxidant power (FRAP) and DPPH radical scavenging capacity. The methanolic extracts of the aerial parts of 8 varieties of Matricaria pubescens were tested. The results indicated that these varieties had strong radical scavenging capacity as well as a strong reducing antioxidant power. The average contents of polyphenols, flavonoids, condensed tannins, hydrolysable tannins and anthocyanins were 1.58 ± 0.33, 38.44 ± 10.77, 0.63 ± 0.2, 1.22 ± 1.55 and 0.39 ± 0.13 mg/g of dry matter, respectively, with the highest contents found in the samples harvested from the region of Ouargla. The Ferric reducing antioxidant power was positively correlated with the contents of hydrolysable tannins which play a major role in the antioxidant properties. Samples were divided into two groups by cluster analysis and variables measured. These results are useful for the selection of varieties and as guidance for their harvest.